ЕСТЕСТВЕННЫЕ ИЗМЕНЕНИЯ РУСЛА НИЖНЕГО ТЕЧЕНИЯ Р. МОСКВЫ И ЕГО ТРАНСФОРМАЦИЯ В УСЛОВИЯХ ИНТЕНСИВНОЙ ХОЗЯЙСТВЕННОЙ ДЕЯТЕЛЬНОСТИ - Каргаполова И.Н.; Завадский А.С. (My University, 2006)
Comparison of vast amount of archive documents helped to reveal the dynamics of channel relief during the last 300 year under the influence of the climatic cyclicity. Certain changes took place due to human impact: runoff regulation by water storage, canalization and runoff transfer, construction material quarrying. Presently the river channel is adapting to new conditions after human intervention. Channel parameters will probably reach optimal values in 100-150 years.
Keywords: 551.4.435.13->556.51(282.247)